No difference in outcomes with 15 mm vs. 20 mm lumen-apposing metal stents for endoscopic ultrasound-guided gastroenterostomy for gastric outlet obstruction: a meta-analysis - Shyam Vedantam; Rahil Shah; Sean Bhalla; Shria Kumar; Sunil Amin (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims We compared outcomes between use of 15 vs. 20 mm lumen-apposing metal stents (LAMSs) in endoscopic ultrasound-guided gastroenterostomy (EUS-GE) for gastric outlet obstruction. Methods Databases were queried for studies that used LAMS for EUS-GE to relieve gastric outlet obstruction, and a proportional meta-analysis was performed. Results Thirteen studies were included. The 15 mm and 20 mm LAMS had pooled technical success rates of 93.2% (95% confidence interval [CI], 90.5%-95.2%) and 92.1% (95% CI, 68.4%-98.4%), clinical success rates of 88.6% (95% CI, 85.4%-91.1%) and 89.6% (95% CI, 79.0%-95.1%), adverse event rates of 11.4% (95% CI, 8.1%-15.9%) and 14.7% (95% CI, 4.4%-39.1%), and reintervention rates of 10.3% (95% CI, 6.7%-15.4%) and 3.5% (95% CI, 1.6%-7.6%), respectively. Subgroup analysis revealed no significant differences in technical success, clinical success, or adverse event rates. An increased need for reintervention was noted in the 15 mm stent group (pooled odds ratio, 3.59; 95% CI, 1.40-9.18; p=0.008). Conclusions No differences were observed in the technical, clinical, or adverse event rates between 15 and 20 mm LAMS use in EUS-GE. An increased need for reintervention is possible when using a 15 mm stent compared to when using a 20 mm stent.